Easily-assembled high-sealing ball valve body forge piece - LIN WEIZHONG; CHEN WANZHU (2023)
The utility model discloses a ball valve body forge piece easy to assemble and high in sealing performance, and relates to the technical field of ball valves, the ball valve body forge piece comprises a valve body, clamping grooves are symmetrically arranged on two side walls of the valve body, a valve cavity matched with a valve core is arranged at the center of an inner cavity of the valve body, and a water outlet pipeline and a water inlet pipeline are respectively arranged on the left side wall and the right side wall of the valve cavity. The water outlet pipeline and the water inlet pipeline are both communicated with the clamping grooves, flange plates are embedded in the clamping grooves, a filtering mechanism is arranged on one side of the water inlet pipeline and comprises a filtering opening and a filtering net, the filtering net is arranged in the filtering opening, and the filtering mechanism is arranged on the water inlet pipeline, so that certain filtering can be carried out, and impurity blocka